PELATIHAN KECEMASAN BERBICARA DI HADAPAN UMUM PADA SISWA SMU - Lukman Nadjamuddin; Ismarli Muis; Abdul Rahmat; Perdana Kusuma (Universitas Negeri Makassar, 2023)
Students generally feel anxious when they are going to do or to anticipate an important task, i.e. speaking in public. Normally, students overcome the feeling of anxiety by trying to calm down, and they believe that this strategy was the best way to reduce anxiety before doing a task (pre-performance anxiety). Several previous studies show that the best alternative way for reducing anxiety is not by calming down, but by reappraising the physiological reaction of anxiety as a feeling of pleasure that arises from doing an enjoyable task as excitement. Individuals who reassess this experience, have better performance and lessen anxiety than individuals who try to calm down. In this study, participants will be trained to change their physical assessment of anxiety-provoking situations, by repeating the phrase